2009
DOI: 10.1590/s1679-62252009000400023
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the Neotropical electric fish Brachyhypopomus draco (Teleostei: Hypopomidae) from southern Brazil

Abstract: The reproductive biology of a population of the weakly electric fish Brachyhypopomus draco from southern Brazil is described. Information is provided on the establishment of the reproductive period in this species and its relations with environmental and feeding factors, as well as on the absolute and relative fecundities, spawning type, sex ratio and sexual dimorphism. The species exhibits a relatively long reproductive period, a relative fecundity of 0.173 oocytes per mg of female total weight, and fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Although Arrington et al (2006) found a significant relationship between lipid liver content and the mesenteric fat index, analysis of the relationship between HSI and GSI in C. temensis segregated by CPV grade, shows that after an initial period of increase in both indices, HSI stabilizes and then drops as GSI increases to its maximum. This effect is even more pronounced in females and is similar to that shown in another Neotropical flood pulse river species, Brachyhypopomus draco (Schaan et al, 2009). In summary, as C. temensis individuals approach the açu form and gametes and gonads mature, HSI begins to decrease while corporal reserves continue to increase.…”
Section: Liver and Reservessupporting
confidence: 80%
See 1 more Smart Citation
“…Although Arrington et al (2006) found a significant relationship between lipid liver content and the mesenteric fat index, analysis of the relationship between HSI and GSI in C. temensis segregated by CPV grade, shows that after an initial period of increase in both indices, HSI stabilizes and then drops as GSI increases to its maximum. This effect is even more pronounced in females and is similar to that shown in another Neotropical flood pulse river species, Brachyhypopomus draco (Schaan et al, 2009). In summary, as C. temensis individuals approach the açu form and gametes and gonads mature, HSI begins to decrease while corporal reserves continue to increase.…”
Section: Liver and Reservessupporting
confidence: 80%
“…Second, although patterns of reserve deposition (specifically regarding liver reserve versus alternate corporal reserve deposition) vary with species and life history parameters, the literature shows that fishes whose reproductive period does not coincide precisely with periods of low food availability or high energy requirements may have offset periods of reserve deposition and consumption between the liver and corporal deposits. When reproductive maturation is disengaged from migration, maintenance or periods of minimal food availability, increases in hepatosomatic index (HSI) are not necessarily synchronized with increases in corporal reserve deposition or utilization (Larson, 1991;Schaan et al, 2009). Further it is suggested that materials essential to gametogenesis are stored in the liver (Craig et al, 2000;Regost et al, 2001) and that body fat is not metabolically essential for reproduction; rather it is used primarily for maintenance during low food or high energy consumption periods, such as winter in temperate zone fishes (Larson, 1991).…”
Section: Liver and Reservesmentioning
confidence: 99%
“…Reproductive biology and life history: Detailed accounts of the reproductive ecology and life history of Brachyhypopomus are available for B. occidentalis from Panama (Hagedorn, 1986;, and for three species from southern subtropical systems: B. bombilla , B. draco (Schaan et al, 2009), and B. gauderio (Giora et al, 2014;Miranda et al, 2008;Quintana et al, 2004;Silva et al, 2007;Silva et al, 2002; (and see species descriptions herein). The reproductive ecology of Amazon and Orinoco species is largely undocumented, although Alves-Gomes (1997) noted spawning preceding seasonal flooding in the rio Branco system of Roraima, Brazil, and Crampton (1996a) observed spawning coincident with the rising-water period and high water period in species from Amazonian floodplains.…”
Section: Functional Biology and Ecology Specializations Associated Wmentioning
confidence: 99%
“…At extreme southern latitudes Brachyhypopomus exhibit several adaptations to the austral winter -including gonadal quiescence, a general reduction in activity and feeding, and an accompanying reduction of the EOD pulse-rate 2014;Schaan et al, 2009;Silva et al, 2002). Some species of Brachyhypopomus appear to live for only one year, with mortality following a terminal reproductive effort -including B. bennetti (Crampton, 1996a) (listed therein as 'B.…”
Section: Functional Biology and Ecology Specializations Associated Wmentioning
confidence: 99%
“…Ecological studies on gymnotiforms are scarce (Lissmann, 1961;Steinbach, 1970;Hagedorn, 1988;Westby, 1988;Alves-Gomes, 1997;Crampton, 1998), and few data on basic aspects of their natural history have been available up to now, most of which consider aspects of their reproduction and feeding biology (Giora et al, 2005;Schaan et al, 2009;Giora et al, 2011). Further, relatively few troglobitic fishes have been studied in detail, focusing on population traits such as population sizes and densities or individual movements and growth (as a life history component) (see Trajano, 2001;Trajano & Bichuette, 2010).…”
Section: Introductionmentioning
confidence: 99%